Measuring the effects of virtual environment design on decision-making - Oberdörfer, Sebastian; Heidrich, David; Birnstiel, Sandra; Latoschik, Marc Erich (2021 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops, VRW 2021, 2021)
Recent research indicates an impairment in decision-making in immersive Virtual Reality (VR) when completing the Iowa Gambling Task (IGT). There is a high potential for emotions to explain the IGT decision-making behavior. The design of a virtual environment (VE) can influence a user's mood and hence potentially the decision-making. In a novel user study, we measure decision-making using three virtual versions of the IGT. The versions differ with regard to the degree of immersion and design of the VE. Our results revealed no significant impact of the VE on the IGT and hence on decision-making.<br
Keywords: HCI design and evaluation methods; Empirical studies in HCI; Human-centered computing; Human computer interaction (HCI); Virtual Reality; Interaction paradigms